PEMBERDAYAAN MASYARAKAT DALAM SEKTOR PERTANIAN DI MA’HAD AL-ZAYTUN BERDASARKAN PERATURAN DAERAH KABUPATEN INDRAMAYU NOMOR 8 TAHUN 2018 DAN MAQASHID SYARIAH - Al Fathin Ramadhan; Abdur Rahim; Muhammad Isa Asyofuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research addresses the issue of low farmer welfare in Indramayu Regency despite the enactment of Regional Regulation Number 8 of 2018 concerning the Protection and Empowerment of Farmers. Ma’had Al-Zaytun plays a significant role as an educational and social institution that integrates Islamic values through community empowerment programs in the agricultural sector. The purpose of this study is to analyze the forms of community empowerment in agriculture at Ma’had Al-Zaytun based on Articles 34 and 46 of the Regional Regulation and the principles of Maqashid Shariah. This study employs a normative juridical approach with library research as the primary method. Data are collected from primary sources such as the Regional Regulation of Indramayu Regency Number 8 of 2018, Maqashid Shariah literature, and the book Al-Zaytun Sumber Inspirasi (ASI), supported by secondary materials from books, journals, and documents. The data are analyzed qualitatively through data reduction, presentation, and conclusion drawing. The results indicate that community empowerment in the agricultural sector based on Article 34 concerning farmer education and training has been effectively implemented through modern cultivation training, integrated pest management, managerial skills, and sustainable farming systems for members of P3KPI. Furthermore, according to Article 46 on financing and capital facilities, Ma’had Al-Zaytun provides access to modern agricultural tools, production capital, superior seeds, fertilizers, and interest-free loans. In line with the Maqashid Shariah principle of Hifdz al-Mal, Ma’had Al-Zaytun strives to protect, manage, and develop agricultural assets productively, sustainably, and fairly to achieve social and economic justice. Keywords: community empowerment, agricultural sector, Ma’had Al-Zaytun, regional regulation, Maqashid Shariah